The Numerical Simulation of Fluid Flow - Castilla, Robert; Vernet, Anton (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book collects the accepted contributions to the Special Issue "The Numerical Simulation of Fluid Flow" in the Energies journal of MDPI. It is focused more on practical applications of numerical codes than in its development. It covers a wide variety of topics, from aeroacoustics to aerodynamics and flow-particles interaction.